A IMPLEMENTATION OF HYPNOTHERAPY METHODS TO IMPROVE AL-QUR’AN MEMORIZATION AT THE INSTITUTE OF NURUL ULUM MERTAK TOMBOK - Mukminah; Hirlan (Universitas Islam Negeri Mataram, 2024)
Memorizing the Al-Qur’an is one part of the activities carried out by special students at Islamic boarding schools. The process of memorizing the Al-Qur’an will certainly have obstacles for those who memorize the Al-Qur’an. To help improve students' memorization of the Al-Qur’an, namely by using the hypnotherapy method. Two factors hinder students from memorizing the Al-Qur’an, namely internal and external factors. So there needs to be an effort to remove these obstacles. Hypnotherapy methods are often used in the world of health. This is in line with practice where hypnotherapy in practice connects the soul and mind. This research aims to describe how the implementation of hypnotherapy methods improves the memorization of the Al-Qur’an at the Nurul Ulum Mertak Tombok Al-Qur’an Memorization Institute. This research uses qualitative methods, to obtain data by observation, interviews, and documentation with informants, namely educators and students. The research results show that the hypnotherapy process goes through several stages, namely pre-induction, induction, deepening, depth level test, suggestion therapy, hypnotherapeutic technique, and termination. The results of this research show that there has been quite a significant change in students memorizing the Al-Qur’an towards increasing their memorization